Dukungan Sosial terhadap Kemunculan Ide Bunuh Diri pada Remaja - Pajarsari, Sri Utami (Widya Cakra: Journal of Psychology and Humanities, 2020)
Suicide is the number 3 cause of death in young people. Teenagers aged 18 to 24 years tend to have suicidal thoughts or ideas with a higher rate than people aged 55 years and over, which is 33% compared to 20%. One of the risk factors for the emergence of suicidal thoughts or ideas is having mental health problems. Adolescence, especially in the late adolescent phase, is the search for identity that involves social interaction or social relations with other people. This article created to find out how social support can influence the emergence of suicide ideas in adolescents. Social support can be obtained from family, friends, and other social environments. Adolescents who get social support or weak family support have a higher risk of committing suicide. The social support that can influence the emergence of suicide ideas is the lack of support from family, friends, and significant others.